Improving Early Childhood Social-Emotional Development through the Mindful Morning Circle Method: Classroom Action Research at ABA 55 Semarang Kindergarten - Fitriyani, Dyah Siti; Agustingrum, Maria Denok Bekti (Proceedings Series on Social Sciences & Humanities, 2025)
This classroom action research investigates the impact of the "Mindful Morning Circle" method on the social-emotional development of early childhood students at ABA Semarang Kindergarten, Indonesia. The study addresses the increasing need for culturally responsive mindfulness strategies within early education, especially in settings with socio-emotional challenges among learners. Conducted over two action cycles, the research involved 10 children aged 5–6 years, including one with hearing impairment. Data were gathered through observation, interviews, field notes, and documentation. The intervention, rooted in mindfulness and Islamic spiritual values, included breathing exercises, guided storytelling, and emotional check-ins. Results indicated a significant improvement in children's emotional regulation, empathy, peer interaction, and classroom engagement. Qualitative analysis revealed themes of increased self-awareness, improved focus, and emotional vocabulary expansion. The findings support the integration of culturally grounded mindfulness practices into daily routines, particularly in Islamic early childhood education settings. This research contributes to the growing literature on social-emotional learning by offering a model that is adaptable, inclusive, and rooted in local values. Future studies may explore scalability and longitudinal outcomes.